Geomorphic and hydrological controls on groundwater dolocrete formation in the semi‐arid Hamersley Basin, northwest Australia. Issue 14 (14th August 2019) - Mather, Caroline C.; Nash, David J.; Dogramaci, Shawan; Grierson, Pauline F.; Skrzypek, Grzegorz
Abstract: Groundwater dolocretes may exert an important geomorphic control on landscape evolution within sub‐humid to arid regions. However, the geomorphic and hydrogeological settings of dolocrete remain poorly described. The hydrochemical conditions of dolomite precipitation in groundwater environments are also not well known. Classic models of dolocrete formation explain dolomite precipitation from highly evolved groundwaters at the terminus of major drainage but do not explain dolocrete distributed in regionally elevated landscapes, upgradient of major drainage. This study investigated the mineralogy, micromorphology and stable carbon and oxygen isotope compositions of three dolocrete profiles within a regionally elevated sub‐basin of the Hamersley Ranges in the Pilbara region of northwest Australia. We sought to establish the environmental and hydrochemical conditions and present a model for dolocrete formation. We found that dolocrete formed within zones of emerging groundwater under saline‐evaporitic conditions within internally draining sub‐basins, most likely during the Late Miocene and Pliocene. Saline‐evaporitic conditions were indicated by: (i) the mineralogy, dominated by dolomite, palygorskite and smectite; (ii) desiccation features and the presence of phreatic and vadose cements, indicative of a shallow fluctuating water table, and; (iii) dolomite δ 18 O values (median = –5.88 ‰). Dolomite precipitation was promoted by evaporation and carbon dioxide degassing from shallow magnesium (Mg)‐rich groundwater. These factors appear to have been the major drivers of dolocrete development without a requirement for significant down‐dip hydrochemical modification. Primary dolomite precipitation was possible due to the presence of microbial extracellular polymeric substances (EPS). EPS provided negatively charged nucleation sites, which bound Mg 2+, overcoming kinetic effects. High microbial activity within groundwater systems suggest these processes may be important for dolocrete formation worldwide and that groundwater dolocretes may be more pervasive in landscapes than currently recognized. © 2019 John Wiley & Sons, Ltd. © 2019 John Wiley & Sons, Ltd. Abstract : A new model is presented for groundwater dolocrete formation in a regionally elevated sub‐basin upgradient of major drainage, as opposed to in a terminal basin setting. The groundwater dolocretes formed under saline‐evaporitic conditions within internally‐draining sub‐basins, mostly likely during the Late Miocene and Pliocene. Evaporation and carbon dioxide degassing from shallow magnesium‐rich groundwater, in the presence of microbial extracellular polymeric substances, promoted primary dolomite precipitation without a requirement for significant down‐dip hydrochemical evolution.